2000
DOI: 10.1093/nar/28.19.3743
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an enhancer and an alternative promoter in the first intron of the alpha-fetoprotein gene

Abstract: In this study we have characterized a positive regulatory region located in the first intron of the alpha-fetoprotein (AFP) gene. We show that the enhancer activity of the region depends on a 44 bp sequence centered on a CACCC motif. The sequence is the target of the two zinc fingers transcription factors BKLF and YY1. The introduction of a mutation destroying the CACCC box impairs the binding of BKLF but improves that of YY1. Moreover, the mutated sequence behaves as a negative control element, suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Variant AFP transcripts identified in rodents were expressed preferentially in hepatic or yolk sac cells (24,25). These suggest that the vAFP transcripts in the human hematopoietic cells are different from ones identified in rat or in mouse not only in their molecular structures, but also in their expression pattern.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Variant AFP transcripts identified in rodents were expressed preferentially in hepatic or yolk sac cells (24,25). These suggest that the vAFP transcripts in the human hematopoietic cells are different from ones identified in rat or in mouse not only in their molecular structures, but also in their expression pattern.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, all variant forms of AFP reported in the previous studies and this study use unique first exons. Because the different usage of the first exon suggests that the vAFP expression is dependent on a unique promotor (24,25), further studies are required to elucidate the hematopoietic cell-specific promotor of vAFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the Afp-GFP transgene within a subpopulation of liver cells may reflect heterogeneity in the onset and level of expression. In addition, the constructs generated for this study lacked an intronic enhancer and alternative promoter known to contribute to Afp expression in the yolk sac and fetal liver (Scohy et al, 2000;Gabant et al, 2002).…”
Section: Endoderm Specificity Of Gfp Expressionmentioning
confidence: 99%
“…5 and 6). More recently it has been shown that the first intron of the Afp gene contains an enhancer and an alternative promoter called P2 (7). The genes of the albumin family are linked in the mammalian genomes, and this conserved organization has been proposed to be important for the developmental expression switch of the genes of the family after birth (8).…”
mentioning
confidence: 99%